(untitled) (Cadernos de Sociomuseologia, 2023)
The collectionism deployed from the XVI century created new paridigms for the investigation of colections. To identify such narratives, linking them to specific environments prepared to care for colletions like museums, is necessary to observe all spheres by wich the collected objects pass, extracting from its morphology, raw material and function the constitutive informations that can reveal its sociocultural identity. This article intends to retrieve and order systematIcally the informations about an indigenus pipe from Mbyá people, starting from this people’s origins and its sociocultural relations until its collecting by the institution that welcomed it. Keywords: Memory; Patrimony; Ethnografic collections; Indigeous ethnology; Museums.